Analisis Tingkat Pencemaran Lingkungan Permukiman Di Sekitar Pasar Mangkang Kota Semarang - Aji Pamurti, Andarina; Maulana, Nur Fajar (Jayapangus Press, 2023)
Mangkang Market in Semarang City is a market with high economic activity. Mangkang Market is located on the pantura road that connects Semarang City with Kendal Regency, so it has high mobility, potentially causing noise and PM 2.5 air pollution in settlements around the market. Market activities also have the potential for water pollution in Kali Bakti. This study aims to determine the level of environmental pollution of settlements living around Mangkang Market. For this purpose, noise measurements, PM 2.5 air quality and water conditions in Kali Bakti were conducted. Measurement of surface water by taking water samples in Kali Bakti was carried out to measure the level of drainage water quality which is a place for domestic wastewater disposal. The water condition in Kali Bakti was measured in the laboratory of Semarang City Environmental Agency. The method in this study uses a descriptive quantitative approach by categorizing based on class or level. The result of noise measurement using Sound Level meter and formula is that the settlement noise is included in the low level of 52.4 dB from the standard 55 dB. While the measurement of PM 2.5 air quality is included in the high pollution category, namely 27 µg / Nm3, from the standard standard of 25 µg / Nm3 based on WHO. And laboratory checks of water in Kali Bakti are included in the medium level of pollution, namely IPj 2,151370942.